Impresi Teknis Penugasan terhadap Beban Tugas Siswa dalam Pembelajaran Daring di Madarasah Aliyah Negeri 1 Nganjuk - Merlin Putri Wulansari (ISLAMIKA, 2021)
Online learning should be an effective learning to reduce the spread of Covid-19. Student assignments should be packaged with creative learning media so that students do not feel burdened. Learning integration is a solution that is applied at Madrasah Aliyah Negeri 1 Nganjuk to overcome learning that does not only focus on the teacher's task. This study uses a qualitative method with a case study approach. Data collection techniques used in this study are observation, interviews and documentation. The research is intended to find out how the technical assignment of students can affect the increase in student assignment load during online learning and determine appropriate and effective solutions in overcoming the increase in student assignment load during online learning at Madarasah Aliyah Negeri 1 Nganjuk.